Deletion of glyceraldehyde‐3‐phosphate dehydrogenase (gapN) in Clostridium saccharoperbutylacetonicum N1‐4(HMT) using CLEAVE™ increases the ATP pool and accelerates solvent production. Issue 5 (19th December 2021) - Monaghan, Taylor I.; Baker, Joseph A.; Krabben, Preben; Davies, E. Timothy; Jenkinson, Elizabeth R.; Goodhead, Ian B.; Robinson, Gary K.; Shepherd, Mark
Summary: The development and advent of mutagenesis tools for solventogenic clostridial species in recent years has allowed for the increased refinement of industrially relevant strains. In this study we have utilised CLEAVE™, a CRISPR/Cas genome editing system developed by Green Biologics Ltd., to engineer a strain of Clostridium saccharoperbutylacetonicum N1‐4(HMT) with potentially useful solvents titres and energy metabolism. As one of two enzymes responsible for the conversion of glyceraldehyde‐3‐phosphate (GAP) to 3‐phosphoglyceric acid in glycolysis, it was hypothesised that deletion of gapN would increase ATP and NADH production that could in turn improve solvent production. Herein, whole genome sequencing has been used to evaluate CLEAVE™ and the successful knockout of gapN, demonstrating a clean knockout with no other detectable variations from the wild type sequence. Elevated solvent levels were detected during the first 24 h of batch fermentation, indicating an earlier shift to solventogenesis. A 2.4‐fold increase in ATP concentration was observed, and quantitation of NAD(P)H derivatives revealed a more reducing cytoplasm for the gapN strain. These findings expand our understanding of clostridium carbon metabolism and report a new approach to optimising biofuel production. Abstract : This article employs a combination of genetic, genomic and microbiological techniques to demonstrate that manipulation of glyceraldehyde‐3‐phosphate activity in a solventogenic clostridium species can enhance butanol and acetone titres. These findings expand our understanding of clostridium carbon metabolism and report a new approach to optimising biofuel production.